5.23. Rozwiąż dany układ równań metodą podstawiania. a) 2(x + y) – 3(x – y) = 4 big| 5 (x+y)-7 big(x-y big)=2 3(2x – y) – 2(x + 4y) = 6 – 10y 0, 5(x – 3y) – (4y – x) + 8 = 0 16 – 2(3x – 5y) = 9y – 2x |20-3(x-2y)=5y+9 b) 4x + 3y = 11, \qquad – 5x + 2y = – 31 2x – 5y = 9, \qquad 4x + 19y = 47 4(3x+y)- Big\\ 3(2x+3y)+ y)-(x-2y)=4y+7x 3y)+5(x-y)=-18 3x-8-(5x-\\ 4-2(x-y)+ x+3y-2(x-\\ 3(4x-y)-1 – 2(x – y) = 4(y + 6) – (5x + 4y) = x – 2y -y)+3x=0 y)-11(x+y)=5-13y

5.23. Rozwiąż dany układ równań metodą podstawiania. a) 2(x + y) – 3(x – y) = 4 big| 5 (x+y)-7 big(x-y big)=2 3(2x – y) – 2(x + 4y) = 6 – 10y 0, 5(x – 3y) – (4y – x) + 8 = 0 16 – 2(3x – 5y) = 9y – 2x |20-3(x-2y)=5y+9 b) 4x + 3y = 11, \qquad – 5x + 2y = – 31 2x – 5y = 9, \qquad 4x + 19y = 47 4(3x+y)- Big\\ 3(2x+3y)+ y)-(x-2y)=4y+7x 3y)+5(x-y)=-18 3x-8-(5x-\\ 4-2(x-y)+ x+3y-2(x-\\ 3(4x-y)-1 – 2(x – y) = 4(y + 6) – (5x + 4y) = x – 2y -y)+3x=0 y)-11(x+y)=5-13y